Duplications upstream and downstream of SHOX identified as novel causes of Leri–Weill dyschondrosteosis or idiopathic short stature. Issue 4 (24th December 2015) - Bunyan, David J.; Baffico, Maria; Capone, Lucia; Vannelli, Silvia; Iughetti, Lorenzo; Schmitt, Sébastien; Taylor, Emma‐Jane; Herridge, Adam A.; Shears, Deborah; Forabosco, Antonino; Coviello, Domenico A.
Abstract : Leri–Weill dyschondrosteosis is a pseudoautosomal dominantly‐inherited skeletal dysplasia ascribed to haploinsufficiency of the SHOX gene caused by deletions, point mutations, or partial duplications of the gene, or to heterozygous deletions upstream or downstream of the intact SHOX gene involving conserved non‐coding cis‐regulatory DNA elements that show enhancer activity. Recently, two SHOX conserved non‐coding element duplications, one upstream and one downstream, were reported in patients referred with idiopathic short stature. To further evaluate the role of these duplications in SHOX ‐related disorders, we describe seven patients (five with Leri‐Weill dyschondrosteosis and two with short stature) all of whom have duplications of part of the upstream or downstream conserved non‐coding element regions, identified by multiplex ligation‐dependent probe amplification. In addition, we show data from 32 patients with an apparently identical downstream duplication that includes a proposed putative regulatory element (identified by multiplex ligation‐dependent probe amplification or array comparative genome hybridization), which results in a variable phenotype from normal to mild Leri–Weill dyschondrosteosis. These additional data provide further evidence that duplications of upstream and downstream long range cis‐regulatory DNA elements can result in a SHOX ‐related phenotype. © 2015 Wiley Periodicals, Inc.